Implementation of Physical Education in the form of Small Game Modifications at SD Negeri 02 Halaban - Isbendral, Isbendral; Zulman, Zulman; Nirwandi, Nirwandi (Yayasan Sekora, 2017)
The purpose of this study was to determine how students' perceptions of the implementation of learning in the form of small game modifications. This arises because during this time students tend not to be motivated towards physical education lessons, so that students do not get physical fitness in participating in learning. This type of research is descriptive. When the research began in December 2010. The study population was all students of SD Negeri 02 Halaban District 50 Kota. Sampling was done by purposive sampling, namely by appointing 60 class IV and V class students. The instrument used to collect data was a questionnaire or questionnaire using the Guttmant scale. Data were analyzed using frequency analysis techniques in the form of percentages. From the data analysis, it was obtained the following research results: the modified variable of the 20 questions posed by the respondent's level of achievement was 69.83%. From these findings, it can be concluded that the level of achievement of the implementation of the small game modification model in the teaching and learning process of Physical Education at Public Elementary School 02 Halaban, 50 Kota Regency is categorized as â€œGoodâ€.